2019
DOI: 10.1109/access.2019.2930717
|View full text |Cite
|
Sign up to set email alerts
|

A Distance-Based Method for Building an Encrypted Malware Traffic Identification Framework

Abstract: The popularity of encryption method brings a great challenge to malware traffic identification. Traditional classes defined by expert experience are usually classified based on the host behaviors of malware, such as banking malware or ransomware, which are often irrelevant to its communication traffic behaviors. It leads to the fact that the boundaries of traffic feature dataset of different malware classes are fuzzy and make these traditional classes unhelpful for classification based on traffic features. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…For the random forest classifiers, their testing time seems to be correlated to a tunable parameter (i.e., the number of trees in the forest), each of which is hand-tuned to optimize the accuracy (800 for Markov chain-based random forest and 200 for TIG-based random forest). It implies that the raw input size (25) to construct the traffic interaction graph is optimized, as described in [11]. A similar tendency is observed in the SVM classifiers.…”
Section: Roc Curves and Auc Valuesmentioning
confidence: 57%
See 3 more Smart Citations
“…For the random forest classifiers, their testing time seems to be correlated to a tunable parameter (i.e., the number of trees in the forest), each of which is hand-tuned to optimize the accuracy (800 for Markov chain-based random forest and 200 for TIG-based random forest). It implies that the raw input size (25) to construct the traffic interaction graph is optimized, as described in [11]. A similar tendency is observed in the SVM classifiers.…”
Section: Roc Curves and Auc Valuesmentioning
confidence: 57%
“…For malware family classification for TLS-encrypted traffic, [9] showed that the L1 multinomial logistic regression classifier with the enhanced flow features can classify TLS-encrypted malware traffic into 1 of 18 classes (i.e., malware families) with a total accuracy of 90.3%. In [25], an XGBoost [26]-based malware family classification framework was proposed with a distance-based clustering method to measure the similarity between malware families. Ref.…”
Section: Malware Detection and Family Classification From Tls-encrypt...mentioning
confidence: 99%
See 2 more Smart Citations
“…In [24], Prasse et al proposed a Long Short-term Memory neural network which uses only observable features of HTTPS traffic (client and host IP addresses and ports, timestamps, data flow volume, and the unencrypted host domain name) for malware classification, claiming it outperforms random forest models in similar applications with a 64% detection rate and 70% precision. The authors of [25] proposed a distance-based, supervised learning solution which suffers from the pitfall of relying on collecting a large amount of traffic data and extracting the features before any analysis can be completed. An approach that analyzes persistent communications, instead of the presence of anomalies within the persistent communication itself, is offered in [26].…”
Section: B Use Of Encryption In Malware Developmentmentioning
confidence: 99%